Construction of sexualities and sexual identities among young Ndebele women - Nkabinde, Simphiwe (Department of Psychology, 2024)
South Africa has a diversity of cultures and cultural practices that influence women's sexualities. However, we do not have sufficient knowledge about how these social and cultural practices shape the constructions of female sexualities and sexual identities within this particular context. Instead, female sexualities were predominantly studied from the western bio-medical paradigm which resulted in pathologised and erroneously prejudicial understandings of African female sexualities as barbaric, risky and sexually victimized. This study sought to explore how young Ndebele women understand their own sexualities. Furthermore, it examined the ways in which socio-cultural factors influence young women's understanding of their sexualities and the role that cultural practices play in how young women make sense of their sexual lives and identities. Six focus group interviews were conducted with forty-one IsiNdebele speaking young women between the ages of fifteen and twenty-four, who resided in different townships and rural villages of former KwaNdebele. Through thematic analysis, the study revealed that the sexual socialization of the girl child by the family unit and schooling system impacts young women's understandings of their bodies and disregards their agency and autonomy to make decisions about their sexual lives. The study found that the isiNdebele female initiation process known as ukuthomba plays a significant role in shaping young women's understanding of their own sexualities. One of the core principles of ukuthomba were to emancipate young women and empower them to be confident, argentic beings in their sexuality and sexual relationships however, societal norms and expectations of what female sexuality ought to look like often contradicted that notion. This study further found that young women sought out sexual relationships with skewed power dynamics because of status and material gain, however this took away their power. Overall, the conflict between indigenous and modern knowledge systems challenged some of the young women when they had to make decisions regarding sexual debut, condom use, child birth, initiating sex or even exercising agency in their sexuality and sexual relationships.